Ferrimagnetic (α-Mn3O4/MnO)@rGO nanocomposite as potential adsorbent for organic pollutant dye - Gangwar A.; Shaw S.K.; Sharma A.; Alla S.K.; Kavita S.; Vasundhara M.; Gupta J.; Barick K.C.; Hassan P.A.; Prasad N.K. (My University, 2025)
Room temperature ferrimagnetic nanocomposite (α-Mn3O4/MnO)@rGO with significant magnetic properties was developed by sol–gel method followed by calcination at higher temperature. X-ray diffraction studies established the formation of phase and HR-TEM images asserted its morphology. The elemental mapping using a HAADF-STEM confirmed the presence of C, O and Mn which was further validated from their interfacial bonding characteristics by FTIR and XPS studies. The UV–visible DRS, Mott-Schottky and impedance results suggested its ability to degrade organic dyes by interacting with reactive oxygen species (ROS) formed via Fenton-type reaction between catalyst and H2O2 or absorbing photon or involving both photo-Fenton type reaction. The catalytic degradation of organic dye, methylene blue (MB) was found to be about 91 % in 15 min and it reached to 97.6 % in next 45 min via H2O2 mediated Fenton-type reaction at ambient temperature, which outperforms the other Mn-O based catalysts. The observed higher catalytic activity could be attributed to the synergistic effects of rGO and α-Mn3O4/MnO nanoparticles. Further, catalytic degradation efficiency of MB was found to be dependent on pH of the medium, concentration of dye and amount of catalyst. Moreover, this nanocatalyst can be reused for degradation of organic dyes due to its inherent magnetic properties. © 2022 Elsevier B.V.